2020
DOI: 10.1037/xhp0000851
|View full text |Cite
|
Sign up to set email alerts
|

Dual target search: Attention tuned to relative features, both within and across feature dimensions.

Abstract: Current models of attention propose that we can tune attention in a top-down controlled manner to a specific feature value (e.g., shape, color) to find specific items (e.g., a red car; feature-specific search). However, subsequent research has shown that attention is often tuned in a context-dependent manner to the relative features that distinguish a sought-after target from other surrounding nontarget items (e.g., larger, bluer, and faster; relational search). Currently, it is unknown whether search will be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 92 publications
0
1
0
Order By: Relevance
“…In addition to target feature and joint feature localization, individual attention can also establish relationship-based ACS, separating target from other non-targets around in a context-dependent manner [13][14]. This relational account suggests that the exact feature values of the target show high variability in the natural environment, bias attention towards the relationship between targets and non-targets may be more helpful for search [15][16][17][18]. It has recently been found that individuals can adapt relationship-based and feature-based ACSs.…”
Section: Relation-based Attentional Control Settingmentioning
confidence: 99%
“…In addition to target feature and joint feature localization, individual attention can also establish relationship-based ACS, separating target from other non-targets around in a context-dependent manner [13][14]. This relational account suggests that the exact feature values of the target show high variability in the natural environment, bias attention towards the relationship between targets and non-targets may be more helpful for search [15][16][17][18]. It has recently been found that individuals can adapt relationship-based and feature-based ACSs.…”
Section: Relation-based Attentional Control Settingmentioning
confidence: 99%
“…;Geng, Diquattro, & Helm, 2017;Hamblin-Frohman & Becker, 2021;Yu & Geng, 2019). In particular, templates can be defined not only by a specific feature value (e.g., orange) but by a feature relation (e.g., "redder" targets), as demonstrated with behavioral (Becker, Folk, & Remington, 2010Becker, Martin, & Hamblin-Frohman, 2019), eye-tracking (Becker, 2010;Becker, Harris, Venini, & Retell, 2014;York, Sewell, & Becker, 2020), and neurophysiological measures (Schönhammer, Grubert, Kerzel, & Becker, 2016). However, these studies generally use a limited but consistent set of stimuli throughout an experiment, to better measure how templates are shaped and optimized through repeated presentations of the target and distractor features.…”
Section: Introductionmentioning
confidence: 99%